If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2a + -3a + 1 = 6 Reorder the terms: 1 + -2a + -3a = 6 Combine like terms: -2a + -3a = -5a 1 + -5a = 6 Solving 1 + -5a = 6 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -5a = 6 + -1 Combine like terms: 1 + -1 = 0 0 + -5a = 6 + -1 -5a = 6 + -1 Combine like terms: 6 + -1 = 5 -5a = 5 Divide each side by '-5'. a = -1 Simplifying a = -1
| 356/16=267/x | | -2x+4x-28=-2x+3x-12 | | 14-y=17 | | 8n+(-6n)= | | 247/26=209/x | | 4r^2-12r-160=0 | | -2x(x+5)=0 | | 8y-3=8y-5 | | 3(z-12)=9 | | 2x-50=62 | | 8n+(-6n)+(-9)-12= | | 20/3n=3/4 | | 1.8+v=3.8 | | 3-t=11 | | -66=r-(-74) | | (7-3i)(-2-5i)= | | P-37/23=5 | | 1996+43w=7385-67 | | x+2x+32=180 | | x-2x+4x+25=-2x+3x+38 | | 7(w-92)=14 | | x/4-1=43 | | 144/150=174.72/x | | 40-12y+-5y=6 | | .375x+12=4 | | 2=t/2 | | N-473=276 | | 20-6n= | | 74-d=61 | | 40-13y-5y=6 | | 59x+1621x-62=42(40x+48) | | 8x+6=4y |